Plasma exposure of a pre-damaged ITER-like plasma facing unit in the WEST tokamak: in-situ and post-mortem measurements. (March 2023) - Corre, Yann; Loewenhoff, Torsten; Richou, Marianne; Brezinsek, Sebastijan; Coenen, Jan; Dejarnac, Renaud; Diez, Mathilde; Fedorczak, Nicolas; Firdaouss, Mehdi; Gaspar, Jonathan; Grosjean, Alex; Gunn, James-Paul; et al.
Highlights: Infrared quantitative thermography. Damaged PFC. ITER like tungsten PFC. heat transfer modelling. Abstract: The consequences of tungsten (W) cracking on divertor lifetime and plasma operation are high priority issues for ITER. One actively cooled ITER-like plasma facing unit (PFU) has been pre-damaged in a High Heat Flux (HHF) facility before its installation in WEST in order to assess the damage evolution after tokamak plasma exposure. The resulting pre-damage exhibits micrometer-size crack network and high roughness on the tungsten monoblock (MB) top surface. A total of 10 MBs, equally distributed on the low and high field sides of the lower divertor, have been pre-damaged among the 35 radially aligned MBs characteristic of the WEST PFU. Subsequent plasma exposure was carried out, from the first breakdown achieved in WEST (in 2017) until the removal of the damaged PFU three years later (2020). On top of the whole WEST plasma exposure (covering C1-C4 experimental campaigns), a dedicated experiment has also been performed in the frame of the EU work program to maximize the power and energy loads on one of the damaged MBs featuring a "crack network" pattern. The MB top surface, including both "crack network" damage and "healthy" (undamaged) areas, was monitored with a high spatial resolution IR camera to detect any potential evolution of the damage pulse after pulse. This paper describes the full plasma exposure achieved in the WEST tokamak (including large number of steady-state and transient heat loading cycles), the dedicated "damaged PFU exposure" experiment together with the experimental results (heat loading on the damaged MBs). Post-mortem measurement reveals significant broadening of the cracks and new cracks in the electron beam loaded area only.